Sizes of insurance premiums and insurance coverage as important elements of the lawyer’s civil liability insurance mechanism: experience of foreign countries - Zaborovskyy, V. V.; Manzyuk, V. V. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
Within the limits of this article, the legal nature of the institute of civil liability insurance of the lawyer is revealed, primarily through the prism of determining the reasonable and fair sizes of both insurance contributions and insurance coverage. Attention is drawn to the fact that determining the size of both insurance premiums and insurance coverage, as important elements of the lawyer’s civil liability insurance mechanism, is perceived as a clear obstacle to the introduction of such an insurance mechanism in Ukraine. It is concluded that the difficulty of fixing the above amounts, primarily in the aspect of determining the optimal ratio between them, in particular, is that, on the one hand, the amount of insurance contributions should not be perceived as a financial burden for the lawyer, and on the other hand, the amount of insurance coverage should in turn, to ensure the property interests of the lawyer’s client. This article is also devoted to clarifying the experience of the legislators of foreign countries (the Republic of Italy, the Federal Republic of Germany, the Republic of Austria, the French Republic, the Republic of Lithuania, Romania, the United States of America and Canada) primarily in determining the minimum (guarantee) amounts of insurance sums. It is concluded that primarily in order to ensure the interests of the lawyer’s client, a number of foreign countries at the legislative level establish minimum (guarantee) amounts of insurance sums, as well as various indicators that affect the determination of this amount in the conditions of mandatory civil liability insurance of lawyers. Attention is drawn to the fact that although foreign countries (in particular, European countries) use different approaches to their definition, we believe that the Ukrainian legislator should fix the minimum amounts of insurance sums, the calculation of which should depend on certain indicators (primarily the form and scope of the lawyer’s activity, duration employment as a lawyer in general).